Regulation of NDVI and ET negative responses to increased atmospheric vapor pressure deficit by water availability in global drylands - Wen, Rihong; Jiang, Peng; Qin, Meiou; Jia, Qingyu; Cong, Nan; Wang, Xiaoying; Meng, Ying; Yang, Feiyun; Liu, Bin; Zhu, Mengyuan; Zu, Jiaxing; Chen, Ning (Frontiers in Forests and Global Change, 2023)
Atmospheric vapor pressure deficit (VPD) has been identified as a major driver of global vegetation dynamics. Drylands are more sensitive to climate change and play an important role in affecting carbon, nitrogen and water cycles. However, we know little about how increasing VPD will affect vegetation growth and evapotranspiration (ET) in the global drylands. Here, we used long-term satellite datasets combined with multiple statistical analyses to examine the response of satellite-derived Normalized Difference Vegetation Index (NDVI), a proxy for vegetation growth, and ET to VPD across the global drylands. We found that the significant negative partial correlation coefficients of the relationships between VPD and NDVI (RVPD-NDVI) and ET (RVPD-ET) were detected in more than 60 % of the drylands. This negative effect was significantly and positively regulated by soil water availability using multiple linear regression (including interaction terms). Moving-window analyses further revealed that temporal changes in RVPD-NDVI and RVPD-ET were positively correlated with changes in the Standardized Precipitation Evapotranspiration Index (SPEI). Areas with increasing RVPD-NDVI and RVPD-ET over time showed an increasing trend in SPEI, whereas the areas with decreasing SPEI showed a negative trend in RVPD-NDVI and RVPD-ET over time. As atmospheric dryness will increase with climate change, this study highlights the importance of reframing how we represent the role of water availability in driving the response of vegetation growth and ET to increasing VPD across the global drylands.